Method for producing group III nitride semiconductor

By performing ammonia treatment, thermal cleaning and nitriding treatment on the sapphire substrate, combined with the crystal core layer formation process, the problem of degradation of crystal quality of the AlN layer is solved, and the manufacturing of high-quality Group III nitride semiconductor is achieved.

CN119816011APending Publication Date: 2025-04-11TOYODA GOSEI CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410939.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when forming an AlN layer, the crystal quality is reduced and it is difficult to control cracks and surface roughness.

Method used

By using ammonia treatment, thermal cleaning and nitriding treatment steps, combined with the crystal core layer formation process, a high-quality Group III nitride semiconductor is formed by supplying gas containing ammonia to the sapphire substrate and thermal cleaning and nitriding treatment at high temperatures.

Benefits of technology

The crystal quality of the Group III nitride semiconductor formed on the sapphire substrate is improved, and cracks and surface roughness are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816011A_ABST
    Figure CN119816011A_ABST
Patent Text Reader

Abstract

Provided is a method for producing a group III nitride semiconductor with which it is possible to form a group III nitride semiconductor having good crystal quality. This method for producing a group III nitride semiconductor comprises: an ammonia treatment step in which a gas containing ammonia is supplied to the surface of a sapphire substrate (10); a thermal cleaning step in which, after the ammonia treatment step, the surface of the substrate (10) is thermally treated in a hydrogen-based atmosphere; a nitriding step of nitriding the surface of the substrate by supplying a gas containing ammonia to the surface of the substrate 10 after the thermal cleaning step; and a crystal nucleus layer formation step for forming a crystal nucleus layer (11) by generating a GaN, AlGaN, or AlN nucleus (11A) on the substrate after the nitriding step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a Group III nitride semiconductor. Background Art

[0002] The wavelength of ultraviolet light of solid-state light-emitting elements using group III nitride semiconductors corresponds to a wavelength band in the range of about 210 to 400 nm. In particular, it is known that UVC (wavelength 100 to 280 nm) can effectively sterilize and disinfect, and the demand for group III nitride semiconductor LEDs that radiate ultraviolet light with a wavelength corresponding to UVC is increasing. Ultraviolet LEDs are composed of an AlN layer formed on a sapphire substrate and an n-layer, a light-emitting layer, and a p-layer composed of AlGaN stacked on the AlN layer.

[0003] In order to form a high-quality AlN layer, it is necessary to nitride the surface of the sapphire substrate and then grow AlN. Non-patent document 1 records that ammonia is supplied to the sapphire substrate to nitride the sapphire substrate, and then AlN is formed on the sapphire substrate. In addition, it is recorded that the nitridation process is carried out while heating from a low temperature to 1200°C.

[0004] Prior art literature

[0005] Patent Literature

[0006] Non-patent literature 1: Mitsuru Funato, Mami Shibaoka and Yoichi Kawakami, "Heteroepitaxy mechanisms of AlN on nitridated c-and a-plane sapphire", JOURNALOF APPLIED PHYSICS 121, 085304 (2017) Summary of the invention

[0007] However, in the method of Non-Patent Document 1, the nitride film (AlN) formed by nitridation treatment is a crystal having a mixed +c plane and -c plane. There is a problem that the quality of the crystal formed on the AlN is reduced, and it is difficult to control the generation of cracks and surface roughness.

[0008] The present invention has been made in view of the above background, and an object of the present invention is to provide a method for producing a Group III nitride semiconductor capable of forming a Group III nitride semiconductor having good crystal quality.

[0009] One embodiment of the present invention is a method for producing a Group III nitride semiconductor, comprising:

[0010] In the ammonia treatment step, a gas containing ammonia is supplied to the surface of the substrate made of sapphire.

[0011] a thermal cleaning step, after the ammonia treatment step, thermally treating the surface of the substrate in a hydrogen-based atmosphere;

[0012] a nitriding treatment step of supplying a gas containing ammonia to the surface of the substrate to nitridate the surface of the substrate after the thermal cleaning step; and

[0013] The crystal nucleus layer forming step is to form a crystal nucleus layer by generating GaN, AlGaN or AlN nuclei on the substrate after the nitriding step.

[0014] In the above method, the sapphire substrate is subjected to ammonia treatment before thermal cleaning, and the surface of the sapphire substrate is nitrided after thermal cleaning. Therefore, the crystal quality of the group III nitride semiconductor formed on the sapphire substrate can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a diagram showing the manufacturing process of the Group III nitride semiconductor in the first embodiment.

[0016] Figure 2 It is a schematic diagram showing the layer structure at each growth stage in Embodiment 1.

[0017] Figure 3 This is a graph showing the time changes of temperature and pressure in the first embodiment.

[0018] Figure 4 This is a graph showing the relationship between the temperature range of the ammonia treatment and the half-peak width of the diffraction line of X-ray diffraction.

[0019] Figure 5 This is a graph showing the relationship between the ammonia treatment time and the half-peak width of the diffraction line of X-ray diffraction.

[0020] Figure 6 This is a graph showing the relationship between the starting temperature of the ammonia treatment and the half-peak width of the diffraction line of X-ray diffraction.

[0021] Figure 7 This is a graph showing the relationship between the hydrogen flow rate of thermal cleaning and the half-peak width of the diffraction line of X-ray diffraction.

[0022] Figure 8 This is a graph showing the relationship between the nitriding treatment time and the half-peak width of the diffraction line of X-ray diffraction.

[0023] Fig. 9 It is a schematic diagram showing the layer structure at each growth stage in the second embodiment.

[0024] Fig.10 This is a graph showing the time change of temperature in the second embodiment.

[0025] Fig.11 This is a graph comparing the half-peak widths of the (002) diffraction line.

[0026] Fig.12 This is a graph comparing the half-peak widths of the (102) diffraction line.

[0027] Explanation of symbols

[0028] 10: Substrate

[0029] 11, 21: Crystal core layer

[0030] 11A, 21A: Nuclear

[0031] 12A: Low-temperature three-dimensional growth layer

[0032] 12B: High temperature three-dimensional growth layer

[0033] 22: Three-dimensional growth layer

[0034] 13, 23: Two-dimensional growth layer DETAILED DESCRIPTION

[0035] The method for manufacturing a Group III nitride semiconductor comprises: an ammonia treatment step, in which a gas containing ammonia is supplied to the surface of a substrate composed of sapphire; a thermal cleaning step, in which, after the ammonia treatment step, the surface of the substrate is thermally treated in an atmosphere mainly composed of hydrogen; a nitridation treatment step, in which, after the thermal cleaning step, a gas containing ammonia is supplied to the surface of the substrate to nitride the surface of the substrate; and a crystal nucleus layer forming step, in which, after the nitridation treatment step, nuclei of GaN, AlGaN or AlN are generated on the substrate to form a crystal nucleus layer.

[0036] In the method for producing the group III nitride semiconductor, the ammonia treatment step may be performed at a temperature of 20° C. to 900° C. This can further improve the crystal quality of the crystal nucleus layer.

[0037] In the method for producing the group III nitride semiconductor, the ammonia treatment step may be performed for 1 second to 60 seconds, thereby further improving the crystal quality of the crystal nucleus layer.

[0038] In the method for producing a group III nitride semiconductor, the ammonia treatment step may be performed at an ammonia partial pressure of 0.001 atm to 0.1 atm and a gas linear velocity of 0.01 m / min to 300 m / min, thereby further improving the crystal quality of the crystal nucleus layer.

[0039] In addition, in the method for producing a group III nitride semiconductor, the thermal cleaning step may be performed at a temperature higher than 900° C. This can further improve the crystal quality of the crystal nucleus layer.

[0040] In the method for producing a group III nitride semiconductor, the nitridation step may be performed for 70 seconds or longer at a temperature lower than that of the thermal cleaning step, thereby further improving the crystal quality of the crystal nucleus layer.

[0041] In addition, the method for manufacturing the group III nitride semiconductor may further include: a low-temperature three-dimensional growth layer forming step, after the crystal nucleus layer forming step, AlGaN or AlN is grown from the core at a temperature lower than that of the crystal nucleus layer forming step, and adjacent crystals from the core are merged to form a low-temperature three-dimensional growth layer; and a high-temperature three-dimensional growth layer forming step, after the low-temperature three-dimensional growth layer forming step, AlGaN or AlN is grown from the low-temperature three-dimensional growth layer at a temperature higher than that of the low-temperature three-dimensional growth layer forming step and lower than that of the crystal nucleus layer forming step to form a high-temperature three-dimensional growth layer. AlGaN and AlN with good crystal quality can be formed.

[0042] (Implementation Method 1)

[0043] 1. Method for manufacturing group III nitride semiconductor

[0044] The method for manufacturing the group III nitride semiconductor in Embodiment 1 is described. It should be noted that the group III nitride semiconductor is formed using the MOCVD method, and as the raw material gas, for example, ammonia is used as the nitrogen raw material gas, TMGa (trimethylgallium) or TEGa (triethylgallium) is used as the Ga raw material gas, TMAl (trimethylaluminum) is used as the Al raw material gas, and hydrogen or nitrogen is used as the carrier gas.

[0045] In the description of the following manufacturing method, reference is made to Figures 1 to 3 . Figure 1 1 is a flowchart showing an initial step (a step before the core 11A is formed) in the manufacturing process of a group III nitride semiconductor. Figure 2 Schematically shows the structure of the layers at each growth stage until the two-dimensional growth layer 13 is formed. Figure 3 This is a graph showing the temporal changes in temperature and pressure and the supply timing of various gases.

[0046] 1-1. Ammonia treatment process

[0047] First, a substrate 10 made of sapphire with a c-plane as the main surface is prepared. The main surface may be an a-plane. In addition, the substrate 10 may have a break angle of 0.1 to 2 degrees in the m-axis direction or the a-axis direction.

[0048] Next, the substrate 10 is placed in a MOCVD device, and vacuuming and hydrogen purge (or nitrogen purge) are performed to reduce the pressure in the MOCVD device ( Figure 3 During the period T11). Figure 3, the case where the pressure is set to 4 kPa is shown.

[0049] Then, the surface of the substrate 10 is treated with ammonia ( Figure 1 Step S1, Figure 3 The ammonia treatment is a treatment in which ammonia is added to hydrogen to form a mixed gas, which is supplied to the MOCVD device, the substrate 10 is heated, and the surface of the substrate 10 is placed in an ammonia atmosphere. Figure 3 In FIG. 1 , as an example of ammonia treatment, a case where the temperature is raised from 200° C. to 700° C. under a pressure of 4 kPa is shown.

[0050] The temperature (substrate temperature) at the start of supply of ammonia may be at least room temperature (eg, 20° C.) and less than 900° C. In Embodiment 1, the ammonia treatment is performed while increasing the temperature, but the maximum temperature is preferably 900° C. or less.

[0051] It should be noted that, in Embodiment 1, the ammonia treatment is performed while the temperature is increased, but it can also be performed at a constant temperature as long as the temperature is between room temperature and 900° C. When the ammonia treatment is performed at a constant temperature, it is more preferably performed at 20 to 900° C. In addition, when the ammonia treatment is performed while the temperature is increased, the temperature at the start is preferably 20 to 900° C., and the temperature at the end is preferably 200 to 900° C.

[0052] The time of the ammonia treatment is preferably 1 to 60 seconds. By being within this range, the crystal quality of the crystal nucleus layer 11 can be further improved. It is more preferably 10 to 50 seconds.

[0053] Since ammonia is corrosive, it is considered that the ammonia treatment causes some modification on the surface of the substrate 10. In addition, since the treatment is performed at a low temperature of 900° C. or less, the decomposition efficiency of ammonia is low, and the surface of the substrate 10 may not be fully nitrided.

[0054] In the ammonia treatment, the partial pressure of ammonia is preferably 0.001 to 0.1 atm, and the flow rate of the gas is preferably 0.01 to 300 m / min. Within this range, the crystal quality of the crystal nucleus layer 11 formed on the substrate 10 can be further improved. A more preferred ammonia partial pressure is 0.01 to 0.05 atm, and a more preferred flow rate is 0.1 to 150 m / min.

[0055] The pressure of the ammonia treatment may be normal pressure, but is preferably reduced pressure, for example, 1 to 90 kPa, preferably 1 to 50 kPa, and more preferably 1 to 20 kPa. Alternatively, the same pressure as that of the thermal cleaning in the next step may be used.

[0056] In Embodiment 1, a mixed gas of hydrogen and ammonia is used, but an inert gas such as nitrogen may be mixed instead of or in addition to hydrogen.

[0057] 1-2. Thermal cleaning process

[0058] Next, thermal cleaning of the surface of the substrate 10 is performed ( Figure 1 Step S2, Figure 3 The thermal cleaning is performed by stopping the supply of ammonia and supplying only hydrogen while continuing to heat the substrate 10. By this thermal cleaning, impurities attached to the surface of the substrate 10 are removed and the surface of the substrate 10 is flattened (see Figure 2 (a)). It is believed that by this thermal cleaning, impurities such as oxides and Si are removed from the surface of the substrate 10, and the Al2O3 surface of the sapphire becomes an Al-rich surface.

[0059] Thermal cleaning is preferably performed at a temperature higher than 900°C. For example, it is performed at a temperature of 1150 to 1300°C for 1 second to 15 minutes. In addition, thermal cleaning can be performed while the temperature is increased or at a constant temperature. Figure 3 , as an example of thermal cleaning, a case where the temperature is raised from 700° C. to 1190° C. at a pressure of 4 kPa is shown.

[0060] The temperature of the thermal cleaning is preferably higher than that of the crystal nucleus layer forming step described later. The more preferred range of the temperature of the thermal cleaning is 1170 to 1250° C., and further preferably 1180 to 1220° C. In addition, the atmosphere may be a hydrogen-based atmosphere, such as a mixed gas containing 80% by volume or more of hydrogen. In addition, the mixed gas is, for example, a mixed gas of hydrogen and nitrogen.

[0061] The pressure may be normal pressure, but is preferably reduced pressure, for example, 1 to 90 kPa, preferably 1 to 50 kPa, and more preferably 1 to 20 kPa.

[0062] The flow rate of hydrogen or a mixture of hydrogen and nitrogen on the substrate 10 can be 5 to 500 m / min (meters per minute), preferably 5 to 300 m / min, and more preferably 5 to 150 m / min. In addition, the flow rate of the mass flow controller is preferably 1 to 30 slm. Cracks in the two-dimensional growth layer 13 can be reduced.

[0063] 1-3. Nitriding process

[0064] Next, the surface of the substrate 10 is nitrided ( Figure 1 Step S3, Figure 3 During the period T14). The nitridation treatment is a treatment in which the surface of the substrate 10 that has become Al-rich is nitrided by lowering the temperature than the thermal cleaning and supplying ammonia in addition to hydrogen. Through the nitridation treatment, one to several monolayers of AlN layers (not shown) are formed on the surface of the substrate 10 as the starting point for nucleus generation. Figure 3In FIG. 1 , as an example of nitriding treatment, the case where the nitriding treatment is performed at a pressure of 4 kPa and a temperature of 1155° C. is shown.

[0065] The temperature of the nitriding treatment is, for example, 1100 to 1220° C., which may be the same temperature as the crystal nucleus layer forming step of the next step. The pressure in the nitriding treatment is the same as that in the ammonia treatment and the thermal cleaning. In addition, the ammonia partial pressure and the gas flow rate are also the same as those in the ammonia treatment. The time of the nitriding treatment is preferably 50 seconds or more. Cracks in the two-dimensional growth layer 13 can be reduced. More preferably, it is 70 to 300 seconds.

[0066] 1-4. Crystal nucleus layer formation process

[0067] Next, ammonia and TMAl are supplied at the same temperature as the nitridation treatment in the previous step or at a lower temperature than the nitridation treatment in the previous step to generate AlN nuclei 11A on the substrate 10 to form a crystal nucleus layer 11 ( Figure 2 (b) Figure 3 During the period T15). Figure 3 In the embodiment 1, the case of a temperature of 1155° C. is shown as an example. The pressure is the same as that in the previous process. Conventionally, the core 11A is formed at about 1000° C., but in the first embodiment, by setting the temperature higher than that, the surface migration of the raw material atoms is increased, and a larger core 11A than before is formed. Thus, the core 11A composed of AlN can be made of high quality.

[0068] Due to the poor lattice mismatch between the core 11A and the substrate 10 made of sapphire, compressive stress is applied to the core layer 11. However, since the lattice mismatch between the core 11A and the substrate 10 is large, the stress is relaxed within a few nm, and the stress at the interface between the substrate 10 and the core 11A is small.

[0069] The crystal nucleus layer 11 is preferably grown to a thickness of 1 to 100 nm. The core 11A can be made sufficiently large. The size and density of the core 11A are preferably within the following ranges.

[0070] The density of the core 11A is preferably 3×10 11 / cm -2 Below. In addition, the size of the core 11A (the average diameter when viewed from above) is preferably 20 to 50 nm. Here, the diameter is the diameter when the core 11A is converted into a circle of the same area. By making the size of the core 11A within such a range, the tensile stress can be sufficiently reduced. In addition, the deviation of the size of the core 11A (the difference between the maximum diameter and the average diameter and the difference between the average diameter and the minimum diameter) is preferably 10 nm or less.

[0071] It is important that the core 11A is large. When the crystal cores merge with each other to form a flat film, tensile stress is generated on its surface. Therefore, if the core size is small and the density is high, the stress generated on the surface when the core merges to form a flat film also becomes large. Therefore, it is necessary to reduce the core density. Therefore, it is effective to increase the core size.

[0072] There is another advantage of low core density. Threading dislocations are formed at the meeting surfaces where cores 11A merge with each other. If the core density is low, the meeting surfaces where cores 11A merge also become fewer. Therefore, by reducing the core density, the formation of threading dislocations can be reduced, and a high-quality crystal film can be formed.

[0073] The preferred growth temperature of the crystal nucleus layer 11 is 1100-1200°C. By setting the temperature in this range, the core 11A can be made large enough. This is because the surface migration of the raw material atoms can be improved. It is more preferably 1125-1190°C, and further preferably 1150-1180°C. It can also be the same temperature as the nitriding treatment in the previous process. By increasing the core 11A, the core density is reduced. Therefore, the interface between the cores 11A is also reduced. The tensile stress generated in the film may be generated when the cores 11A merge with each other and become flat, but by reducing the core density as described above, the stress generated after the cores 11A merge with each other can be reduced.

[0074] The growth rate is preferably 5 to 100 nm / min. By increasing the growth rate, the diameter of the core 11A can be increased. It is more preferably 10 to 80 nm / min, and even more preferably 20 to 70 nm / min.

[0075] The V / III ratio is preferably 5 to 500. By setting the V / III ratio to such a range, the growth rate can be controlled to the above range.

[0076] It should be noted that it is possible to form AlN with a -c plane on the nitrided substrate 10, but a +c plane can be formed depending on the growth conditions such as a low V / III ratio and a high growth rate as the growth conditions of the core 11A. Generally, a crystal layer with a +c plane is preferred. Even if +c and -c are mixed in the crystal core layer 11, as long as the proportion of -c is small, +c will dominate through the growth process, and it will eventually become a crystal layer with a surface having only a +c plane. As another possibility, AlON may be formed on the surface of AlN at temperatures above 1100°C. It is known that AlON reverses polarity, and even if AlN with a -c plane is formed on the nitrided substrate 10, it is believed that the polarity is reversed due to AlON to obtain a +c plane.

[0077] 1-5. Low-temperature three-dimensional growth layer formation process

[0078] When the crystal nucleus layer 11 grows to a predetermined thickness, the supply of TMAl is stopped and the crystal nucleus layer 11 is cooled to a temperature lower than that in the step of forming the crystal nucleus layer 11 ( Figure 3 Then, when the low temperature three-dimensional growth layer 12A is cooled to its growth temperature, the supply of TMAl is started again. Thus, the crystal grows three-dimensionally starting from the core 11A of the crystal nucleus layer 11, and the crystals grown from the adjacent cores 11A merge to form the low temperature three-dimensional growth layer 12A ( Figure 2 (c) Figure 3 During the period T17). Figure 3 In the example, the case of a temperature of 1000° C. is shown. The pressure is the same as that in the previous step. By coalescing the nuclei 11A, threading dislocations can be reduced, and a high-quality low-temperature three-dimensional growth layer 12A can be formed.

[0079] Here, since the growth temperature of the low-temperature three-dimensional growth layer 12A is set to a temperature lower than the growth temperature of the core 11A, the stress applied to the layer up to the low-temperature three-dimensional growth layer 12A becomes a compressive stress due to the difference in linear expansion coefficient with the substrate 10. Generally, the case where cracks are generated in the growth layer is a case of tensile stress. Since the compressive stress based on the difference in linear expansion coefficient is generated in the layer up to the low-temperature three-dimensional growth layer 12A, cracks can be suppressed.

[0080] In addition, by lowering the temperature, the low-temperature three-dimensional growth layer 12A can be grown slowly, and the low-temperature three-dimensional growth layer 12A grown starting from the core 11A can also be merged slowly. Tensile stress may be generated when the three-dimensional core 11A merges to form a two-dimensional flat film, but since the low-temperature three-dimensional growth layer 12A is slowly grown as described above, even if the low-temperature three-dimensional growth layer 12A on the core 11A merges to form a continuous film, the three-dimensional surface shape is maintained due to low-temperature growth, so cracks caused by tensile stress generated in the film can also be suppressed.

[0081] The low-temperature three-dimensional growth layer 12A is preferably grown thicker than the crystal nucleus layer 11, for example, preferably grown to a thickness of 200 to 500 nm. By fully merging the core 11A as a starting point in a manner from a core shape to a film shape, the threading dislocation density can be reduced. Furthermore, the thicker the low-temperature three-dimensional growth layer 12A, the larger the three-dimensional surface with unevenness can be made. Thus, by promoting lateral growth in the next step, the threading dislocation can be bent and the threading dislocation propagating to the surface of the growth layer can be reduced. A more preferred thickness is 250 to 400 nm, and a further preferred thickness is 250 to 350 nm.

[0082] The growth temperature of the low-temperature three-dimensional growth layer 12A is preferably 900 to 1100° C. By setting the temperature to 900° C. or higher, impurities are less likely to enter the crystal, and light absorption can be reduced. The temperature is more preferably 950 to 1050° C., and even more preferably 975 to 1025° C.

[0083] In addition, the growth rate of the low-temperature three-dimensional growth layer 12A is slower than the growth rate of the crystal nucleus layer 11. By slowing down the growth rate and slowly merging with the nucleus 11A as the starting point, dislocations can be effectively reduced. In addition, the formation of tensile stress generated when the nuclei 11A merge with each other to form a continuous film can be alleviated. The growth rate is preferably 2 to 20 nm / min. More preferably, it is 2 to 15 nm / min, and further preferably, it is 2 to 10 nm / min.

[0084] In addition, the V / III ratio of the low temperature three-dimensional growth layer 12A is greater than the V / III ratio of the crystal nucleus layer 11, and is preferably 500 to 2000. The growth rate can be controlled within the above range, more preferably 750 to 1750, and even more preferably 1000 to 1500.

[0085] 1-6. High-temperature three-dimensional growth layer formation process

[0086] When the low temperature three-dimensional growth layer 12A grown from the nucleus 11A is fully merged and the low temperature three-dimensional growth layer 12A grows to a predetermined thickness, the growth temperature is set higher than the growth temperature of the formation process of the low temperature three-dimensional growth layer 12A and lower than the growth temperature of the formation process of the crystal nucleus layer 11, and a high temperature three-dimensional growth layer 12B is further grown on the low temperature three-dimensional growth layer 12A ( Figure 2 (d)). The pressure is the same as in the previous step.

[0087] The high temperature three-dimensional growth layer 12B is a layer grown to smoothly transition from the three-dimensional growth of the low temperature three-dimensional growth layer 12A to the two-dimensional growth of the two-dimensional growth layer 13. The high temperature three-dimensional growth layer 12B is a three-dimensional growth that grows faster in the lateral direction than the low temperature three-dimensional growth layer 12A. The growth temperature of the high temperature three-dimensional growth layer 12B is higher than that of the low temperature three-dimensional growth layer 12A, so the lateral growth is faster than that of the low temperature three-dimensional growth layer 12A, which can further promote the merging of crystals. As a result, by bending the threading dislocation in the lateral direction, the threading dislocation propagating toward the surface can be reduced, and a crystal film with a low threading dislocation density can be obtained.

[0088] Here, the high temperature three-dimensional growth layer 12B is formed at a higher temperature than the low temperature three-dimensional growth layer 12A, and due to the difference in linear expansion coefficient with the substrate 10, tensile stress is generated in the crystal layer up to the high temperature three-dimensional growth layer 12B when the low temperature three-dimensional growth layer 12A is grown. Therefore, the high temperature three-dimensional growth layer 12B may not be formed as a completely flat film, but may be formed as a three-dimensional surface partially having pits and small planes, thereby relieving the tensile stress generated on the surface and growing.

[0089] The high temperature three-dimensional growth layer 12B is preferably grown thicker than the low temperature three-dimensional growth layer 12A, for example, preferably grown to a thickness of 750 to 2000 nm. If it is within this range, the merging of crystals can be further promoted and the threading dislocation density can be further reduced. The more preferred thickness is 1000 to 1750 nm, and more preferably 1250 to 1500 nm.

[0090] The growth temperature of the high temperature three-dimensional growth layer 12B is preferably 1050 to 1200° C. By setting the temperature in this range, the growth mode can be effectively switched from three-dimensional growth to two-dimensional growth. The temperature is more preferably 1075 to 1175° C., and even more preferably 1100 to 1150° C.

[0091] In addition, the growth rate of the high temperature three-dimensional growth layer 12B is faster than the growth rate of the low temperature three-dimensional growth layer 12A and is lower than the growth rate of the crystal nucleus layer 11, preferably 5 to 50 nm / min. By setting the growth rate to this range, the crystals are slowly merged, and the change of tensile stress generated on the surface of the crystal layer is alleviated, thereby suppressing the generation of cracks when the crystals merge. It is more preferably 10 to 40 nm / min, and even more preferably 15 to 30 nm / min.

[0092] In addition, the V / III ratio of the high temperature three-dimensional growth layer 12B is smaller than the V / III ratio of the low temperature three-dimensional growth layer 12A and is greater than the V / III ratio of the crystal nucleus layer 11, preferably 100 to 1000. The growth rate can be controlled within the above range, more preferably 150 to 700, and further preferably 200 to 500.

[0093] 1-7. Two-dimensional growth layer formation process

[0094] When the high temperature three-dimensional growth layer 12B grows to a predetermined thickness, ammonia, TMAl, and TMGa are supplied at the same temperature as or higher than the temperature in the step of forming the high temperature three-dimensional growth layer 12B to form a two-dimensional growth layer 13 composed of AlN or AlGaN containing Ga (see Figure 2 (e)). The pressure is the same as in the previous step.

[0095] When Ga is supplied during AlN growth, Ga atoms with higher surface migration than Al atoms promote the lateral growth of the AlN growth mode and lead to two-dimensional growth. Therefore, the crystal can be flattened by the two-dimensional growth layer 13. In addition, the supply of Ga increases continuously and stepwise over time. Thus, the lateral growth rate is slowly increased, and the change in tensile stress generated when the crystals merge is alleviated, thereby suppressing the generation of cracks in the two-dimensional growth layer 13.

[0096] The amount of Ga supplied is controlled by the molar ratio of TMGa to TMAl. The molar ratio of TMGa to TMAl is preferably 0.05 to 0.5, more preferably 0.08 to 0.4, and even more preferably 0.1 to 0.3.

[0097] The ratio of TMGa is very high, but Ga is not actually doped into AlN at the above ratio. This is because Ga atoms evaporate more easily on the AlN surface than Al atoms, so even if the molar ratio of the raw gas is 0.3, only a few percent of Ga atoms are actually doped into the AlN crystal. The higher the growth temperature, the more Ga atoms evaporate preferentially, so the number of Ga atoms doped into the AlN crystal decreases further. Although it depends on the growth temperature and other conditions, AlN grown within the above molar ratio range 1-x Ga x The Ga solid phase ratio of N is x=about 0.01 to 0.1%.

[0098] By applying a continuous, step-wise inclination within the above molar ratio range, the inclination is applied in such a way that the Ga supply amount increases over time. By supplying Ga, the two-dimensional growth layer 13 changes from AlN to a mixed crystal of AlN and GaN (Al 1- x Ga x N). Here, the Ga composition is preferably 0.01 to 0.1.

[0099] The two-dimensional growth layer 13 is preferably grown to a thickness greater than that of the high-temperature three-dimensional growth layer 12B, for example, preferably grown to a thickness of 750 to 2000 nm. If it is within this range, the surface of the two-dimensional growth layer 13 can be fully flattened. For example, the surface roughness RMS can be 0.5 to 5 nm. A more preferred thickness is 1000 to 1750 nm, and further preferably 1250 to 1500 nm.

[0100] The preferred growth temperature of the two-dimensional growth layer 13 is 1100 to 1200° C. If the temperature is within this range, the two-dimensional growth layer 13 can be sufficiently flattened. It is more preferably 1120 to 1190° C., and further preferably 1140 to 1180° C. The same temperature as that of the formation process of the crystal nucleus layer 11 and the formation process of the high-temperature three-dimensional growth layer 12B can be used.

[0101] In addition, the growth rate of the two-dimensional growth layer 13 is greater than the growth rate of the high-temperature three-dimensional growth layer 12B and less than the growth rate of the crystal nucleus layer 11, preferably 5 to 50 nm / min. If the growth rate is within this range, the growth rate is slow enough to ease the change in tensile stress caused by the flattening of the crystal and suppress the generation of cracks. It is more preferably 10 to 40 nm / min, and even more preferably 15 to 30 nm / min.

[0102] In addition, the V / III ratio of the two-dimensional growth layer 13 is less than the V / III ratio of the high-temperature three-dimensional growth layer 12B and greater than the V / III ratio of the crystal nucleus layer 11, preferably 50 to 500. The growth rate can be controlled within the above range, more preferably 100 to 400, and even more preferably 150 to 300.

[0103] Then, semiconductor layers can be continuously grown on the two-dimensional growth layer 13 to produce light-emitting elements or the like, or the production can be terminated at the stage of growing the two-dimensional growth layer 13 and used as a template substrate. In addition, it can be used as a template for the substrate 10 to be peeled off by laser lift-off (LLO).

[0104] In the first embodiment, the switching from the formation of the core 11A to the formation of the two-dimensional growth layer 13 is controlled by the growth temperature, but it may be controlled by the growth rate. The growth rate may be controlled by, for example, the growth temperature and the V / III ratio.

[0105] As described above, according to the method for manufacturing a group III nitride semiconductor of embodiment 1, the crystal quality of the nucleus layer 11 can be improved. Although the reason for the improvement in crystal quality is not clear, it can be inferred as follows. If ammonia treatment is performed before thermal cleaning, it is believed that since ammonia is corrosive, some modification occurs on the surface of the substrate 10. Therefore, it is believed that the effect of separating impurities, oxides or particles from the surface of the substrate 10 is improved during thermal cleaning. In this way, impurities on the surface of the substrate 10 can be further reduced. As a result, it is believed that high-quality AlN can be formed on the surface of the substrate 10 in the nitridation treatment after thermal cleaning, and the crystal quality of the nucleus layer 11 formed on the AlN is also improved.

[0106] 2. Experimental results

[0107] Next, various experimental results of Embodiment 1 are described.

[0108] Experiment 1

[0109] After the substrate 10 was subjected to ammonia treatment, thermal cleaning, and nitridation treatment in sequence, a crystal nucleus layer 11, a low-temperature three-dimensional growth layer 12A, a high-temperature three-dimensional growth layer 12B, and a two-dimensional growth layer 13 were formed in sequence from the substrate 10 side on the substrate 10 to prepare a sample. The temperature range in the ammonia treatment was changed to prepare three types of samples. In addition, for comparison, the same sample was also prepared except that the ammonia treatment was not performed.

[0110] Temperature and pressure Figure 3As shown in the graph. In addition, the growth rate of the crystal nucleus layer 11 is 30nm / min, and the thickness is 50nm, the growth rate of the low-temperature three-dimensional growth layer 12A is 4nm / min, and the thickness is 250nm, the growth rate of the high-temperature three-dimensional growth layer 12B is 18nm / min, and the thickness is 1300nm, and the growth rate of the two-dimensional growth layer 13 is 18nm / min, and the thickness is 1400nm. In addition, in the two-dimensional growth layer 13, the molar ratio of TMGa to TMAl is continuously changed from 13% to 30%.

[0111] The rocking curve measurement in X-ray diffraction of the two-dimensional growth layer 13 of the produced sample was performed to obtain the full width at half maximum (FWHM) of the (002) diffraction line and the (102) diffraction line. Figure 4 This is a graph showing the relationship between the temperature range of the ammonia treatment and the half-peak width. The temperature range of the ammonia treatment is three cases: the case of increasing the temperature from 200°C to 400°C, the case of increasing the temperature from 200°C to 900°C, and the case of increasing the temperature from 200°C to 1190°C.

[0112] like Figure 4 As shown, for the (102) diffraction line, the half-peak width is smaller than that without ammonia treatment in any temperature range. In addition, the half-peak width is slightly larger when the temperature is increased from 200°C to 1190°C than in other temperature ranges. For the (002) diffraction line, the wider the temperature range and the higher the maximum temperature, the larger the half-peak width. The results show that in order to improve the crystal quality of the two-dimensional growth layer 13, the temperature range is preferably from 200°C to 400°C or from 200°C to 900°C. In addition, from the results, it can be seen that the ammonia treatment is preferably below 900°C.

[0113] Experiment 2

[0114] The ammonia treatment time was varied and samples were prepared in the same manner as in Experiment 1. The ammonia treatment time was the heating time from 200°C and the heating rate was 3 to 5°C / s. Then, the half maximum width (FWHM) of the (002) diffraction line and the (102) diffraction line was determined in the same manner as in Experiment 1.

[0115] Figure 5 is a graph showing the relationship between the treatment time of ammonia treatment and the half-peak width. Figure 5 As shown in the figure, for the (102) diffraction line, the half-peak width decreases significantly as the treatment time increases until the treatment time is about 60 seconds. When the treatment time exceeds 60 seconds, the half-peak width slowly increases as the treatment time increases. In addition, for the (002) diffraction line, the half-peak width increases as the treatment time increases. From this result, it can be seen that in order to improve the quality of the crystal, the treatment time of the ammonia treatment is preferably 1 to 60 seconds.

[0116] Experiment 3

[0117] The temperature at the start of the ammonia treatment was changed in various ways, and samples were prepared in the same manner as in Experiment 1. The heating time for the ammonia treatment was 20 seconds, and the heating rate was the same as in Experiment 2. Then, the half maximum width (FWHM) of the (002) diffraction line and the (102) diffraction line was determined in the same manner as in Experiment 1.

[0118] Figure 6 is a graph showing the relationship between the temperature at the start of ammonia treatment and the half-peak width. Figure 6 As shown in the figure, for the (102) diffraction line, the half-peak width decreases with the increase of temperature until about 700°C, and when it exceeds this time, the half-peak width increases with the increase of temperature. In addition, for the (002) diffraction line, the half-peak width increases slowly with the increase of temperature until about 700°C, and when it exceeds this time, the half-peak width increases greatly with the increase of temperature. The results show that in order to improve the quality of the crystal, the temperature at the beginning of the ammonia treatment is preferably 100 to 700°C.

[0119] Experiment 4

[0120] The flow rate of hydrogen gas during the thermal cleaning was changed to various values, and samples were prepared in the same manner as in Experiment 1. Then, in the same manner as in Experiment 1, the full width at half maximum (FWHM) of the (002) diffraction line and the (102) diffraction line was determined.

[0121] Figure 7 This is a graph showing the relationship between the flow rate and half-peak width of hydrogen gas in thermal cleaning. Figure 7 As shown, for the (102) diffraction line, the half-peak width increases with the increase of the flow rate. In addition, for the (002) diffraction line, the half-peak width decreases with the increase of the flow rate. In addition, the cracks in the two-dimensional growth layer 13 decrease as the flow rate decreases. The results show that in order to improve the crystal quality, the flow rate of hydrogen in thermal cleaning is preferably 1 to 30 slm.

[0122] Experiment 5

[0123] The treatment time of the nitriding treatment was changed in various ways, and samples were prepared in the same manner as in Experiment 1. Then, in the same manner as in Experiment 1, the full width at half maximum (FWHM) of the (002) diffraction line and the (102) diffraction line was determined.

[0124] Figure 8 This is a graph showing the relationship between the treatment time of the nitriding treatment and the half peak width. Figure 8As shown, for the (102) diffraction line, the half-peak width decreases as the treatment time increases until about 120 seconds, and when this time is exceeded, the half-peak width increases as the treatment time increases. In addition, for the (002) diffraction line, the half-peak width slowly increases as the treatment time increases. In addition, when the treatment time is more than 50 seconds, the cracks in the two-dimensional growth layer 13 decrease as the treatment time becomes longer, and no cracks are generated when the treatment time is more than 150 seconds. The results show that in order to improve the crystal quality, the treatment time of the nitriding treatment is preferably more than 70 seconds.

[0125] (Variation of Implementation Method 1)

[0126] As the core 11A in Embodiment 1, AlGaN or GaN can be used instead of AlN. If GaN or AlGaN is used, the lattice constant difference with sapphire as the substrate 10 is larger, and the strain relaxation at the interface between the substrate 10 and the core 11A becomes larger. In addition, when the core 11A is made of AlGaN or GaN, the Al composition of the lattice constant of the low-temperature three-dimensional growth layer 12A formed thereon is higher than the core 11A, so the low-temperature three-dimensional growth layer 12A grown on the core 11A is subjected to tensile strain. This is because the grown crystal is formed to match the lattice constant of the substrate. Therefore, the compressive strain generated in the low-temperature three-dimensional growth layer 12A later caused by the thermal stress of the substrate and the crystal layer generated when the growth is completed and the temperature reaches room temperature can be alleviated.

[0127] In addition, in the strain relaxation at the interface between the substrate 10 and the core 11A, the core 11A is not formed in a film shape but is formed discretely, so the generation of cracks is suppressed. In addition, the low-temperature three-dimensional growth layer 12A formed on the crystal core layer 11 receives tensile stress from the crystal core layer 11 due to the lattice constant difference, but since it is three-dimensional growth, the generation of cracks caused by tensile stress is suppressed. As a result of the above, the threading dislocation density of the two-dimensional growth layer 13 can be reduced.

[0128] In addition, if the core 11A is made of GaN or AlGaN, the core 11A can be enlarged due to the surfactant effect of Ga, and the core density can be reduced. As mentioned above, if the core density is small, the tensile stress generated on the surface when the cores 11A are combined to form a flat film can be reduced. In addition, the number of meeting surfaces of the cores 11A combined becomes small, the formation of threading dislocations can be reduced, and a high-quality crystal film can be formed.

[0129] The core 11A may be Al-doped GaN. Compared with GaN, the core 11A is preferably AlGaN, and the Al composition is preferably 60% to 98%. This can further relax the strain and further increase the size of the core 11A. More preferably, it is 60% to 98%.

[0130] When the core 11A is GaN or AlGaN, it becomes easy to separate the substrate 10 by laser lift-off. That is, since the band gap energy is smaller than that of AlN, it becomes easy for the crystal core layer 11 to absorb laser. In addition, since the melting point of Ga is much lower than that of Al, when the crystal core layer 11 is decomposed by laser irradiation, Ga becomes liquid. Therefore, when the crystal core layer 11 contains Ga, the substrate 10 can be easily separated. In this way, when the core 11A is GaN or AlGaN, the crystal core layer 11 is effective as a sacrificial layer for laser lift-off.

[0131] When the core 11A is GaN or AlGaN, the size of the core 11A is preferably 20 to 100 nm. By setting the size of the core 11A to be within this range, the tensile stress can be sufficiently reduced. In addition, the deviation of the size of the core 11A (the difference between the maximum diameter and the average diameter and the difference between the average diameter and the minimum diameter) is preferably 20 nm or less.

[0132] In addition, when the core 11A is GaN or AlGaN, the thickness of the crystal nucleus layer 11 is preferably 5 to 100 nm. Compared with the case where the core 11A is AlN, the core 11A becomes larger, so the crystal nucleus layer 11 also becomes thicker. As a result of the enlargement of the core 11A, the quality of the crystal layer formed after the core 11A can be further improved. The more preferred thickness of the crystal nucleus layer 11 is 5 to 50 nm. The higher the composition of Ga in the core 11A and AlGaN, the easier it is for the crystal to move through annealing, and it is also easier to enlarge the core 11A through solid phase growth. The size of the core 11A before the three-dimensional growth layer is grown can also be increased by annealing to reduce the density.

[0133] When the core 11A is made of GaN or AlGaN, the density of the core 11A is preferably 3×10 11 / cm -2 Since the core 11A is larger than that of AlN, the density of the core 11A is also smaller than that of AlN. A more preferred core density is 1.5×10 11 / cm -2 Below, more preferably 1×10 11 / cm -2 In addition, when the core 11A is GaN or AlGaN, the core 11A can be enlarged by annealing. That is, the core density can be made 1×10 11 / cm -2 the following.

[0134] In the first embodiment, the low temperature three-dimensional growth layer 12A is AlN, but is not limited to AlN and may be AlGaN. However, from the viewpoint of strain relaxation and crystallinity, the difference between the Al composition of the low temperature three-dimensional growth layer 12A and the Al composition of the crystal nucleus layer 11 is preferably 40% or less.

[0135] In the first embodiment, the high temperature three-dimensional growth layer 12B is AlN, but is not limited to AlN and may be AlGaN. However, from the viewpoint of strain relaxation and crystallinity, the difference between the Al composition of the high temperature three-dimensional growth layer 12B and the Al composition of the low temperature three-dimensional growth layer 12A is preferably 30% or less.

[0136] In Embodiment 1, the two-dimensional growth layer 13 is AlN, but is not limited to AlN and may be AlGaN. However, from the viewpoint of strain relaxation and crystallinity, the difference between the Al composition of the two-dimensional growth layer 13 and the Al composition of the high-temperature three-dimensional growth layer 12B is preferably 20% or less.

[0137] In addition, when the device formed on the two-dimensional growth layer 13 is a light-emitting device, the crystal layer below the two-dimensional growth layer 13 needs to be made into an Al composition that does not absorb light. When the device formed on the two-dimensional growth layer 13 is an ultraviolet light-emitting LED, the Al composition of the two-dimensional growth layer 13 is preferably the same as or greater than the Al composition of the n-type layer of the LED.

[0138] In summary, most of the device structure is formed by an Al composition lower than the Al composition of the two-dimensional growth layer 13. In order to alleviate the strain of the device structure, it is preferred to change the lattice mismatch in stages. The Al composition of the layers after the three-dimensional growth layer 12 other than the crystal nucleus layer 11 is preferably reduced in stages. By doing so, the strain applied to the device structure can be alleviated.

[0139] As the Al composition of the core 11A becomes lower, the lattice constant changes from AlN to GaN. That is, the lattice constant in the plane becomes larger. Therefore, the three-dimensional growth layer 12 having an Al composition larger than the Al composition of the core 11A formed on the core 11A is subjected to tensile strain from the core 11A. As the Al composition of the core 11A becomes lower, the lattice constant in the plane of the three-dimensional growth layer 12 tends to become larger. The growing three-dimensional growth layer 12 is subjected to tensile strain, and the possibility of crack formation increases. Therefore, as mentioned above, there is an optimal value for the difference in Al composition between the core 11A and the three-dimensional growth layer 12. When the growth ends and the temperature becomes room temperature, due to the difference in thermal expansion coefficient with the substrate 10 composed of sapphire, the tensile strain of the three-dimensional growth layer 12 formed during the growth becomes compressive strain. However, as in the growth, the larger the lattice constant of the core 11A, the more relaxed the compressive strain generated in the three-dimensional growth layer 12 at room temperature.

[0140] In addition, when the core 11A is GaN or AlGaN, the thickness of the two-dimensional growth layer 13 is preferably 0.5 to 5 μm. The surface of the two-dimensional growth layer 13 can be sufficiently flattened. For example, the surface roughness RMS can be 0.5 to 2 nm. The more preferred thickness of the two-dimensional growth layer 13 is 1 to 3 μm.

[0141] In addition, even when the core 11A is made of GaN or AlGaN, the threading dislocation density of the two-dimensional growth layer 13 can be 5×10 11 cm -2 In the following, a high-quality crystal can be obtained. In addition, the half-peak width (FWHM) of the (002) diffraction line measured by the rocking curve in the X-ray diffraction of the two-dimensional growth layer 13 can be, for example, 100 to 300 arcsec, and the half-peak width of the (102) diffraction line can be, for example, 300 to 600 arcsec. This is because the half-peak width can be sufficiently reduced by reducing the threading dislocation density.

[0142] In addition, when the core 11A is made of GaN or AlGaN, the growth conditions such as the growth temperature and growth rate of each layer may be in the same range as that of the first embodiment.

[0143] (Implementation Method 2)

[0144] A method for producing a group III nitride semiconductor in Embodiment 2 is described below. Fig. 9 , 10 . Fig. 9 It is a diagram schematically showing the configuration of each layer at each growth stage until the two-dimensional growth layer 23 is formed. Fig.10 This is a graph showing the time change of temperature and the supply timing of various gases.

[0145] In the method for producing a group III nitride semiconductor in the second embodiment, first, the surface of the substrate 10 is subjected to an ammonia treatment ( Fig.10 period T21), followed by thermal cleaning ( Fig. 9 (a) Fig.10 The various conditions of ammonia treatment and thermal cleaning are the same as those in the first embodiment.

[0146] Next, the nitriding treatment temperature is cooled to the next step. Fig.10 period T23), and then nitriding treatment ( Fig.10 During the period T24), the temperature is, for example, 350 to 650°C. Fig.10 In the embodiment, the case where the treatment is performed at 390° C. is shown as an example. The nitriding treatment may be performed during cooling. The nitriding treatment may be performed under the same conditions as the nitriding treatment in the first embodiment except for the temperature.

[0147] Next, ammonia and TMAl are supplied at the same temperature as in the nitridation treatment of the previous step to generate AlN nuclei 21A on the substrate 10 to form a crystal nucleus layer 21 ( Fig. 9 (b) Fig.10It should be noted that the temperature may be different from that of the nitriding treatment as long as it is in the range of 350 to 650°C.

[0148] Next, the temperature is raised to the growth temperature of the three-dimensional growth layer 22 ( Fig.10 During the period T26), the solid phase growth is promoted by annealing the core 21A of the crystal core layer 21 and the core 21A becomes columnar. The temperature is raised to 1100-1200° C. Then, ammonia and TMGa are supplied to grow GaN on the crystal core layer 21 to form a three-dimensional growth layer 22.

[0149] Next, the temperature is made higher than that of the growth of the three-dimensional growth layer 22, and GaN is two-dimensionally grown on the three-dimensional growth layer 22 to form a two-dimensional growth layer 23. By increasing the growth temperature, the migration of the raw materials is promoted and the lateral growth is accelerated, thereby achieving two-dimensional growth. It is also possible to accelerate the lateral growth and achieve two-dimensional growth by increasing the V / III ratio instead of increasing the temperature.

[0150] It should be noted that in Embodiment 2, GaN is grown as the three-dimensional growth layer 22 and the two-dimensional growth layer 23, but any group III nitride semiconductor is sufficient. However, AlGaN with a low Al composition is preferred. For example, AlGaN with an Al composition of less than 20%. GaN as shown in Embodiment 2 is particularly preferred. Unlike AlGaN and AlN with a high Al composition, AlGaN and GaN with a low Al composition can be easily controlled to grow laterally by temperature and V / III ratio. This is because Ga migrates faster than Al. Therefore, even if the three-dimensional growth layer has large bumps and depressions, it can be easily flattened by the two-dimensional growth layer.

[0151] As described above, in the method for manufacturing a group III nitride semiconductor in the second embodiment, since the ammonia treatment is performed before the thermal cleaning and the nitridation treatment is performed after the thermal cleaning, the crystal quality of the crystal nucleus layer 21 can be improved even when the crystal nucleus layer 21 is formed at a low temperature. Therefore, the crystal quality of the group III nitride semiconductor, especially GaN, formed on the crystal nucleus layer 21 can be improved.

[0152] Next, various experimental results of Embodiment 2 are described. After the substrate 10 is subjected to ammonia treatment, thermal cleaning, and nitridation treatment in sequence, a crystal nucleus layer 21, a three-dimensional growth layer 22, and a two-dimensional growth layer 23 are formed on the substrate 10 in sequence from the substrate 10 side to produce a sample (hereinafter referred to as an embodiment). In addition, for comparison, ammonia treatment is not performed, and a sample is produced in the same manner as in the embodiment (hereinafter referred to as a comparative example). The temperature is as follows Fig.10 as shown in the chart.

[0153] The rocking curve of the two-dimensional growth layer 23 of the produced sample in X-ray diffraction was measured, and the full width at half maximum (FWHM) of the (002) diffraction line and the (102) diffraction line was obtained. Fig.11, 12 This is a graph comparing the half-peak widths in Examples and Comparative Examples. Fig.11 is the half-peak width of the (002) diffraction line, Fig.12 is the half-peak width of the (102) diffraction line.

[0154] like Fig.11 As shown, for the half-peak width of the (002) diffraction line, there is not much change in the embodiment and the comparative example. On the other hand, for the half-peak width of the (102) diffraction line, the half-peak width of the embodiment is smaller than the half-peak width of the comparative example. As can be seen from the results, by performing ammonia treatment before thermal cleaning and nitridation treatment after thermal cleaning, the crystal quality can be improved even when the crystal nucleus layer 21 is formed at a low temperature. Compared with embodiment 1, the effect of improving the half-peak width is small, but it is confirmed that the same effect can be obtained even if the growth temperature of the core 21A is low. From the comparison between embodiment 1 and embodiment 2, when high-quality cores are formed at high temperatures, it is possible that the effect of substrate surface treatment performed by ammonia treatment, thermal cleaning, and nitridation treatment is higher.

Claims

1. A method for producing a group III nitride semiconductor, comprising: In the ammonia treatment step, a gas containing ammonia is supplied to the surface of the substrate made of sapphire. a thermal cleaning step, after the ammonia treatment step, thermally treating the surface of the substrate in an atmosphere mainly composed of hydrogen, a nitridation treatment step of supplying a gas containing ammonia to the surface of the substrate to nitridate the surface of the substrate after the thermal cleaning step; and The crystal nucleus layer forming step is to form a crystal nucleus layer by generating GaN, AlGaN or AlN nuclei on the substrate after the nitridation step.

2. The method for producing a Group III nitride semiconductor according to claim 1, wherein: The ammonia treatment step is performed at a temperature of 20°C to 900°C.

3. The method for producing a Group III nitride semiconductor according to claim 1, wherein: The ammonia treatment step is performed for 1 second to 60 seconds.

4. The method for producing a group III nitride semiconductor according to claim 1, wherein: The ammonia treatment step is performed at a partial pressure of ammonia of 0.001 atm to 0.1 atm and a linear velocity of gas of 0.01 m / min to 300 m / min.

5. The method for producing a Group III nitride semiconductor according to claim 1, wherein: The thermal cleaning process is performed at a temperature above 900°C.

6. The method for producing a Group III nitride semiconductor according to claim 1, wherein: The nitridation process is performed for more than 70 seconds at a temperature lower than the temperature of the thermal cleaning process.

7. The method for producing a Group III nitride semiconductor according to any one of claims 1 to 6, wherein: Further having: a low temperature three-dimensional growth layer forming step of growing AlGaN or AlN from the core at a temperature lower than that in the crystal nucleus layer forming step and merging adjacent crystals from the core to form a low temperature three-dimensional growth layer after the crystal nucleus layer forming step, and A high temperature three-dimensional growth layer forming step, after the low temperature three-dimensional growth layer forming step, at a temperature higher than the temperature of the low temperature three-dimensional growth layer forming step and lower than the temperature of the crystal nucleus layer forming step, AlGaN or AlN is grown from the low temperature three-dimensional growth layer to form a high temperature three-dimensional growth layer.